2017
DOI: 10.1038/s41598-017-00143-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of proteome and histone post-translational modifications in heat shock protein 90 inhibition-mediated bladder cancer therapeutics

Abstract: Heat shock protein 90 (HSP90) inhibition is an attractive strategy for cancer treatment. Several HSP90 inhibitors have shown promising effects in clinical oncology trials. However, little is known about HSP90 inhibition-mediated bladder cancer therapy. Here, we report a quantitative proteomic study that evaluates alterations in protein expression and histone post-translational modifications (PTMs) in bladder carcinoma in response to HSP90 inhibition. We show that 5 HSP90 inhibitors (AUY922, ganetespib, SNX2112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…As a result of the absence of H4K20me3 has been positively correlated with the development of cancers (Pogribny et al, 2007[ 22 ]; Balakrishnan and Milavetz, 2010[ 1 ]). In the present study, the H4K20me3 level increased following the low-/high-dose GA treatment for 6 h and low-dose 17-DMAG for 6 h, whereas it decreased in the cells treated with GA and 17-DMAG for 24 h. Our results are consistent with those of Li et al (2017[ 19 ]). They demonstrated that H4K20me3 and H4K12ac levels increased in a 5637 bladder cancer cell line following treatment with HSP90 inhibitors (AUY922, STAT9090, and SNX-2112).…”
Section: Discussionsupporting
confidence: 93%
“…As a result of the absence of H4K20me3 has been positively correlated with the development of cancers (Pogribny et al, 2007[ 22 ]; Balakrishnan and Milavetz, 2010[ 1 ]). In the present study, the H4K20me3 level increased following the low-/high-dose GA treatment for 6 h and low-dose 17-DMAG for 6 h, whereas it decreased in the cells treated with GA and 17-DMAG for 24 h. Our results are consistent with those of Li et al (2017[ 19 ]). They demonstrated that H4K20me3 and H4K12ac levels increased in a 5637 bladder cancer cell line following treatment with HSP90 inhibitors (AUY922, STAT9090, and SNX-2112).…”
Section: Discussionsupporting
confidence: 93%
“…Epigenetic modifying drugs display substantially modified potency depending on cellular HDJ2 status. While previous studies have indicated the association between proteomic changes and histone PTMs in response to Hsp90 inhibitor treatment in bladder carcinoma cells, no such association has been shown for HDJ2 and Histone PTMs [64]. Interestingly, vorinostat was the only drug that was synergistic to HDJ2 inhibition.…”
Section: Discussionmentioning
confidence: 90%
“…Proteome analysis has been used to study the effects and molecular mechanisms of novel potential drugs for BC. Using the 5637 urinary BC cell line, Li et al [ 62 ] evaluated the effect of five heat shock protein 90 (HSP90) inhibitors (AUY922, ganetespib, SNX2112, AT13387, and CUDC305) in vitro , followed by quantitative proteome analysis at the global and histone post-translational modification levels. HSP90 inhibitors suppress cell proliferation and growth in a dose and time-dependent manner.…”
Section: Applying Proteomics To Bc Researchmentioning
confidence: 99%